2014
DOI: 10.1371/journal.pone.0102873
|View full text |Cite
|
Sign up to set email alerts
|

Gene Networks of Fully Connected Triads with Complete Auto-Activation Enable Multistability and Stepwise Stochastic Transitions

Abstract: Fully-connected triads (FCTs), such as the Oct4-Sox2-Nanog triad, have been implicated as recurring transcriptional motifs embedded within the regulatory networks that specify and maintain cellular states. To explore the possible connections between FCT topologies and cell fate determinations, we employed computational network screening to search all possible FCT topologies for multistability, a dynamic property that allows the rise of alternate regulatory states from the same transcriptional network. The sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 112 publications
(128 reference statements)
0
37
0
Order By: Relevance
“…It is intended to represent at the cell population level cells on their way to differentiation from the stem-cell state as balls rolling down a scenery of bifurcating valleys, the last subdivisions of which end in fully differentiated states. It has been revisited by Sui Huang and colleagues in a series of articles [128,129,130,132,131,133,134,135,136,203,204], which link the bifurcations occurring between the valleys of the epigenetic landscape to bistable -or multistable [81] -switches in ordinary differential equations of systems biology representing the expression of antagonistic genes, such as PU.1 and GATA1 for the choice between myeloid and erythroid fates in the haematopoietic differentiation tree [46,111,136]. Sui Huang proposes, reversing the quote of Theodosius Dobzhansky [69], that "nothing in evolution makes sense except in the light of systems biology" [132].…”
Section: Evolution In a Given Genome: Waddington's Epigenetic Landscamentioning
confidence: 99%
“…It is intended to represent at the cell population level cells on their way to differentiation from the stem-cell state as balls rolling down a scenery of bifurcating valleys, the last subdivisions of which end in fully differentiated states. It has been revisited by Sui Huang and colleagues in a series of articles [128,129,130,132,131,133,134,135,136,203,204], which link the bifurcations occurring between the valleys of the epigenetic landscape to bistable -or multistable [81] -switches in ordinary differential equations of systems biology representing the expression of antagonistic genes, such as PU.1 and GATA1 for the choice between myeloid and erythroid fates in the haematopoietic differentiation tree [46,111,136]. Sui Huang proposes, reversing the quote of Theodosius Dobzhansky [69], that "nothing in evolution makes sense except in the light of systems biology" [132].…”
Section: Evolution In a Given Genome: Waddington's Epigenetic Landscamentioning
confidence: 99%
“…On an intracellular level, GA (or the related Monte Carlo simulation) is often used to simulate stochastic fluctuations in transcriptional regulator numbers [24,61]. These types of simulations can be used to determine likelihood of state transitions under varying amounts of noise [52] or to thoroughly analyze the GRNs potential landscape under a single noise condition [56].…”
Section: Theories and Computation Of Con-trolmentioning
confidence: 99%
“…For example, Yao et al identified a minimal circuit to generate bistability from a simplified Rb-E2F network which regulates the initiation of DNA replication [79]. Faucon et al looked for instances of possible ways in which a three-gene network could exhibit multistability [52]. Additional work has been done to demonstrate the role that small motifs play in enhancing network stability [80].…”
Section: Multistability Of Grnsmentioning
confidence: 99%
“…Self-stimulation is a common property of master switches in gene regulation and other biological signaling systems [22,17,23,24]. In fact, the CDM is a candidate model of biological switches that exhibit multi-stability (co-existence of multiple stable equilibria) [25][26][27][28][29]. At the ecological level, self-stimulation can be regarded as a characteristic of individuals or populations for increasing fitness and avoiding extinction.…”
Section: Introductionmentioning
confidence: 99%